2017
DOI: 10.1186/s13287-016-0454-5
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA Braveheart promotes cardiogenic differentiation of mesenchymal stem cells in vitro

Abstract: BackgroundMesenchymal stem cells (MSCs) have limited potential of cardiogenic differentiation. In this study, we investigated the influence of long noncoding RNA Braveheart (lncRNA-Bvht) on cardiogenic differentiation of MSCs in vitro.MethodsMSCs were obtained from C57BL/6 mice and cultured in vitro. Cells were divided into three groups: blank control, null vector control, and lncRNA-Bvht. All three groups experienced exposure to hypoxia (1% O2) and serum deprivation for 24 h, and 24 h of reoxygenation (20% O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 42 publications
(54 reference statements)
0
49
0
Order By: Relevance
“…The Chinese Academy of Medical Sciences also explored the improvement of cardiac function by MSCs regulated by matrix-derived factor 1 (SDF1a) [48] and CXC chemokine receptor 4 (CXCR4) [49]. Sun Yat-sen University researched the effects of exons (Exo) [50], the TGF-β superfamily [51], the long noncoding RNA brave heart (lncRNA-Bvht) [52], apelin [53] and granulocyte colony stimulating factor (G-CSF) [54] on the proliferation, differentiation and vascularization of MSCs. The functions of the transcription factors islet-1 (ISL1) [55] and platelet brin (PRF) [56] in regulating the repair of myocardial infarction by MSCs have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese Academy of Medical Sciences also explored the improvement of cardiac function by MSCs regulated by matrix-derived factor 1 (SDF1a) [48] and CXC chemokine receptor 4 (CXCR4) [49]. Sun Yat-sen University researched the effects of exons (Exo) [50], the TGF-β superfamily [51], the long noncoding RNA brave heart (lncRNA-Bvht) [52], apelin [53] and granulocyte colony stimulating factor (G-CSF) [54] on the proliferation, differentiation and vascularization of MSCs. The functions of the transcription factors islet-1 (ISL1) [55] and platelet brin (PRF) [56] in regulating the repair of myocardial infarction by MSCs have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Since ncRNAs are central to gene regulation and cellular fates, it can be speculated that most of the EV-mediated regulatory roles elicited in cells/organs are mediated through ncRNAs (18,37). Indeed, ncRNAs are expressed in tissue-specific manner, precisely regulated and actively involved in variety of developmental processes (43)(44)(45)(46)(47)(48)(49)(50), and the lineage specific commitments of stem cells and the maintenance of their characteristic features such as pluripotency, self-renewal, differentiation, and efficiency of cellular reprogramming are largely regulated by ncRNAs (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Thus, the ncRNAs may govern the equilibrium between pluripotency and differentiation in stem cells, as well as lineage specific fate decisions (61,62).…”
Section: Stem Cell-derived Ncrnamentioning
confidence: 99%
“…Recently, Hou et al showed the importance of Bvht in promoting the cardiogenic differentiation of MSC. Overexpression of Bvht in MSC isolated from mouse bone marrow showed a better cardiogenic differentiation and importantly inhibition of MesP1 significantly attenuated the transdifferentiation of MSC overexpressed with Bvht . Being a relatively newcomer to the family of lncRNA, the role of Bvht on CPCs and diabetes is still not known, although the evidence suggests Bvht as a strong candidate requiring further studies.…”
Section: Epigenetic Mechanisms Regulating Cardiac Stem/progenitor Cellsmentioning
confidence: 99%